Fracture penis: rare occurrence - Yadav, Akhilesh Kumar; Dwivedi, Sankalp; Bassi, Sagar; Singh, Sunil Kumar (International Surgery Journal, 2018)
Fracture Penis is not usual. It is a tear in the tunica albuginea of the corpora cavernosa with or without involvement of corpus spongiosum and urethra. The usual cause is abrupt bending of the erect penis by blunt trauma, most commonly during sexual intercourse. A crackling sound, pain, detumescences, bruising, swelling, and bleeding per urethra are the common symptoms reported by the patients. Early surgical management is treatment of choice. Diagnosis of Penile Fracture refers to a rupture of the corpus cavernosum induced by blunt trauma to erect penis. Mainly diagnosed clinically from their stereotypical crackling sound from the erect penis at the moment of injury, rapidly followed by acute swelling, pain and penile deformity. Treatment recommendations include immediate exploration and repair. Surgical repair requires evacuation of hematoma, identification of tear, repair of the tear and ligation of any disrupted vasculature. Long term complications after repair include penile deviation, painful intercourse, painful erection and erectile dysfunction. The diagnosis of penile fracture is mostly clinical. Based on physical examination and typical crackling sound at the time of injury. Prompt surgical exploration and repair are advocated in almost all cases. Immediate surgery reduces long term complication which is post-traumatic penile curvature.